Clinical characteristics and outcomes in pulmonary manifestations of systemic sclerosis: Contribution from pulmonary hypertension and interstitial lung disease severity - Ruchika A. Sangani; Justin K. Lui; Kari R. Gillmeyer; Marcin A. Trojanowski; Andreea M. Bujor; Michael P. LaValley; Elizabeth S. Klings (Pulmonary Circulation, 2022)
Abstract Patients with systemic sclerosis complicated by both pulmonary hypertension (SSc‐PH) and interstitial lung disease (SSc‐PH‐ILD) have poor prognosis compared to those with SSc‐PH or SSc‐ILD alone. Little is known of how ILD severity affects outcomes in those with SSc‐PH, or how PH severity affects outcomes in those with SSc‐ILD. Herein, we aimed to delineate clinical features of patients with SSc‐PH and SSc‐ILD and determine to what degree PH and ILD severity contribute to mortality in patients with SSc. We conducted parallel retrospective studies in cohorts of patients with SSc‐PH and SSc‐ILD. We categorized ILD severity by pulmonary function testing and PH severity by cardiopulmonary hemodynamics. Our primary outcome was all‐cause mortality from time of PH or ILD diagnosis for the SSc‐PH and SSc‐ILD cohorts, respectively. We calculated adjusted risks of time to all‐cause mortality using Cox proportional hazards models. In patients with SSc‐PH, severe ILD (HR: 3.54; 95% CI: 1.05, 11.99) was associated with increased hazards for all‐cause mortality. By contrast, mild and moderate ILD were not associated with increased mortality risk. In patients with SSc‐ILD, both moderate (HR: 2.65; 95% CI: 1.12, 6.31) and severe PH (HR: 6.60; 95% CI: 2.98, 14.61) were associated with increased hazards for all‐cause mortality, while mild PH was not. Through our parallel study design, the risk of all‐cause mortality increases as severity of concomitant ILD or PH worsens. Therapies that target slowing disease progression earlier in the disease course may be beneficial.